From Screens to Playgrounds: Promoting Active Lifestyles in Children Through Traditional Games - Rizky Sugianto Putri; Citra Hennida; Salma Faiza Malika; Firlie Najah Salamah; Alfonsus Arya Gading Fitzyolan; Elok Indriani; Dava Bagas Primusandi (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT Advancements in technology have led to a sedentary lifestyle among children. This situation hampers their growth and development and may increase the risk of non-communicable diseases (NCDs) such as diabetes, obesity, and cardiovascular diseases. It will affect Indonesia’s fragile human resources and strain the healthcare budget. This community service programme aims to support the realisation of an Indonesia Bugar 2045, as expressed by President Prabowo. We utilise traditional games to encourage children to be more active and spend more time outdoors. Our methods include a combination of traditional game roadshows, educational sessions, and focus group discussions. Participants in this activity comprise 40 fourth-grade students, four teachers, and 11 parents from SDN Simokerto V, Surabaya. The community service implementation achieved three outcomes: (1) increased knowledge and awareness among teachers and parents regarding the link between a sedentary lifestyle and the risk of NCDs in children; (2) introduction of three types of traditional games that improve motor skills and cognition, in collaboration with our community service partner, Kampoeng Dolanan; and (3) seventeen variables of anthropometric data and physical performance of 10- to 11-year-old children, which can serve as a foundation for further research on growth and development. The implications of this activity include fostering a mindset among children, parents, and teachers that outdoor physical activity is vital for optimal growth and development and for preventing NCDs in children. As a result, teachers and parents can create a range of more inventive activities both at school and at home. Moreover, it encourages children to engage in more physical activity at an affordable cost through traditional games. Keywords: Anthropometry, Non-Communicable Disease (NCD), Sedentary Lifestyle, Traditional Games.